A Statistical Study of the Decreased TEC Region During Summer at Northern High Latitudes - Jian‐ping Wang; Bei‐chen Zhang; Qing‐yu Zhang; Shun‐rong Zhang; Qing‐he Zhang; Guo‐jun Wang; Jian‐jun Liu (Geophysical Research Letters)
Abstract Based on the vertical Total Electron Content (TEC) data observed by the Global Navigation Satellite System in the northern hemisphere, a large area of low plasma density during summer at high latitudes, termed decreased TEC region, was investigated statistically between 2014 and 2024. Compared with the classical depleted structures that usually occur in the nighttime F region at high latitudes during winter, decreased TEC region is usually found in the sunlit polar cap ionosphere during summer. The decreased TEC region is predominantly located in regions above 70° magnetic latitude for moderate and high solar activity. The lower‐TEC region is biased towards the dawn and midnight sectors. Along the 18:25–06:25 Magnetic Local Time meridian, the depth of the decreased TEC region reached 7.6TECu in 2014. The decreased TEC region is deeper for higher Kp (Kp > 2) than for low Kp (Kp ≤ 2).